Pengelolaan Program Usaha Kesehatan Sekolah - Wiwi Suyanti; Nur Sasongko , Rambat; Connie (Manajer Pendididikan, 2023)
This study aims to describe the management of the school health effort program at Darul Fikri Integrated Islamic Elementary School in Arga Makmur, North Bengkulu. This research used descriptive qualitative method. The research subjects were the principal, the head of student affairs, and the school health effort supervising teacher. The research data were obtained from interviews, observations, and documentation. Data analysis includes data reduction, data presentation, verification, and conclusion drawing. Based on the results of the study, it can be concluded that the management of the school health effort program at Darul Fikri Integrated Islamic Elementary School in Arga Makmur, North Bengkulu has contributed to improving the health of students, teachers, school community, and school environment.